PERAN MASYARAKAT DALAM MELAKSANAKAN PILKADA SERENTAK 2020 DENGAN ADANYA PANDEMI COVID-19 SESUAI UNDANG-UNDANG NOMOR 10 TAHUN 2016 - Murary, Weron (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Concurrent regional head elections in Indonesia will be held for the fourth time in September 2020, but there have been changes due to the Covid-19 pandemic, so that the results of these changes have been determined by the general election commission on 9 December 2020. The community has a very important role in organizing democratic parties such as regional head elections. Therefore, the community cannot be separated from the election because it is a complete unit where the community is the main factor and determines the success of the implementation of regional head elections. The research used by researchers is normative legal research, which is the most widely conducted research. This is because research is only sufficient to do in the workspace, without bothering to dig up data from the community. The data that has been obtained from the results of this study are then analyzed on the basis of theory, both data sourced from primary data and secondary data and analysis using qualitative analysis.The results show that, the role of the community in direct regional head elections is to elect their regional leaders, where the community must be actively involved in supervising regional head elections, the important role played by the community can be by providing information about suspected violations, whether they have been committed. Pilkada administrators, either provincial or district / city KPUs, as well as pilkada participants. Regional head elections or regional elections in 2020, in 270 regions that will carry out a celebration or democratic party to elect governors and deputy governors, regents and deputy regents, mayors and deputy mayors, the community leaves everything to the authorities of the provincial, district / city KPU, DKPP, and Bawalse so that the 2020 regional elections will be better and very satisfying for the community.